2005
DOI: 10.1093/ajcn/82.6.1298
|View full text |Cite
|
Sign up to set email alerts
|

The effect of breastfeeding on mean body mass index throughout life: a quantitative review of published and unpublished observational evidence

Abstract: Mean BMI is lower among breastfed subjects. However, the difference is small and is likely to be strongly influenced by publication bias and confounding factors. Promotion of breastfeeding, although important for other reasons, is not likely to reduce mean BMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
273
0
9

Year Published

2007
2007
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 392 publications
(307 citation statements)
references
References 62 publications
22
273
0
9
Order By: Relevance
“…Nevertheless, a cohort study done with Brazilian children did not arrive at the same conclusion. 14 According to Owen et al, 28 the difference in obesity prevalence observed between breastfed and not breastfed children is small, and probably influenced by the publishing bias and confusing factors. It is, therefore, a controversial issue.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, a cohort study done with Brazilian children did not arrive at the same conclusion. 14 According to Owen et al, 28 the difference in obesity prevalence observed between breastfed and not breastfed children is small, and probably influenced by the publishing bias and confusing factors. It is, therefore, a controversial issue.…”
Section: Discussionmentioning
confidence: 99%
“…Owen et al 14 carried out another meta-analysis of studies of infant breastfeeding and BMI at later ages, this time including published and unpublished data and comparing only the mean BMI in different breastfeeding categories. Considering all published and unpublished results, the mean BMI among breastfed children was only slightly lower than that of nonbreastfed children (-0.04; 95% CI: -0.05; -0.02).…”
Section: Discussionmentioning
confidence: 99%
“…96 The critical window for hypernutrition may extend further into postnatal life, as numerous clinical studies, summarized in systematic reviews and meta-analyses, 33,[97][98][99] have shown that rapid weight gain during early infancy is associated with susceptibility to obesity in adulthood. Such rapid weight gain is often associated with formula feeding, and some [100][101][102] but not all 103 observational studies and metaanalyses have found that breast-feeding is protective against obesity in later life. Similarly, studies that have manipulated the composition of formula feeds have shown protective effects of slower growth against later cardiovascular risk factors in adolescence.…”
Section: The 'Early-life Hypernutrition' Pathwaysmentioning
confidence: 99%